2005
DOI: 10.1128/aac.49.7.2753-2759.2005
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide Resistance in Campylobacter jejuni and Campylobacter coli : Molecular Mechanism and Stability of the Resistance Phenotype

Abstract: A collection of 23 macrolide-resistant Campylobacter isolates from different geographic areas was investigated to determine the mechanism and stability of macrolide resistance. The isolates were identified as Campylobacter jejuni or Campylobacter coli based on the results of the hippurate biochemical test in addition to five PCR-based genotypic methods. Three point mutations at two positions within the peptidyl transferase region in domain V of the 23S rRNA gene were identified. About 78% of the resistant isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
135
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(144 citation statements)
references
References 50 publications
6
135
3
Order By: Relevance
“…The most prevalent are the mutations at positions 2074 and 2075 (domain V) in the rrn gene, which encodes for 23S rRNA (Gibreel et al, 2005). Transversion A2075G is the most commonly found, in most cases, in homozygosis where the three copies of rrn gene possess the mutation (Gibreel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent are the mutations at positions 2074 and 2075 (domain V) in the rrn gene, which encodes for 23S rRNA (Gibreel et al, 2005). Transversion A2075G is the most commonly found, in most cases, in homozygosis where the three copies of rrn gene possess the mutation (Gibreel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5]. However, there is little information available on the characteristics of the resistance mechanism of EM-resistant C. coli isolates from food-producing animals in Japan.…”
mentioning
confidence: 99%
“…It is possible that additional genes in the vicinity of aspA, or in other genomic regions, are of C. jejuni origin and that some of these genes may be related to the extensively documented scarcity of erythromycin resistance in C. jejuni from meat animals (1, 3, 8, 13). C. jejuni can be transformed to erythromycin resistance in the laboratory, using as donor DNA the 23S rRNA fragment from a resistant C. coli strain that harbors the A2075G erythromycin resistance determinant (14). However, it is possible that other C. jejuni genetic determinants negatively impact the competitive fitness of these erythromycinresistant organisms in natural environments or in the animal host.…”
Section: Discussionmentioning
confidence: 99%
“…IVSs are absent from all three 23S rRNA gene copies of C. jejuni NCTC 11168 (32) but were detected in other strains of C. jejuni and C. coli (29,33,41) and were also identified in all three copies of the 23S rRNA gene in the recently sequenced genome of C. coli RM2228 (12). When present, the IVS is located only 891 nucleotides (nt) upstream from the site in the 23S rRNA gene where a point mutation (A2075G) has been associated with high-level resistance to erythromycin in Campylobacter (12,14,20). Surveys of C. jejuni from broilers showed that only a minority of strains (approximately 10%) contained IVSs (29,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation